Chairs as Structures in Egon Schiele’s Aesthetics. Egon Schiele’Place in Wittgenstein’s Vienna - Carmona Escalera, Carla (Nómadas. Critical Journal of Social and Juridical Sciences, 2011)
This paper is part of a larger project that tries to give to Egon Schiele’s oeuvre the place it deserves in what was called by Allan Janik and Stephen Toulmin ’Wittgenstein’s Vienna’. We intend to establish certain correlations between Schiele’s aesthetic vision and Ludwig Wittgenstein’s philosophy. We share the interdisciplinary approach of Janik and Toulmin. Just as they got close to Wittgenstein’s philosophical problems by taking into account the historical, philosophical and cultural context to which he belonged, we make use of Schiele’s contemporary investigations in different areas of knowledge in order to get a more adequate account of his paintings. Following Wittgenstein’s mostly ignored move towards art criticism, we will proceed our investigation through a close analysis and critique of a selection of paintings. Specifically we will be studying Schiele’s use of chairs, understanding them as a compositional device of his pictorial language. The aim of this article is to show how his use of chairs illustrates some of the battles fought by his contemporaries.